Characterization of charge heterogeneity of antibody -drug conjugate by anion-exchange chromatofocusing - Thallaj, Nasser (Latakia University Journal -Medical Sciences Series, 2023)
An anion-exchange chromatofocusing method was developed for the analysis of charge heterogeneity of antibody-drug conjugates. Different chromatographic conditions were evaluated including pre-gradient volume, column temperature, pH of start and elution buffers, and addition of pharmalytes 8-10.5. The charge isoforms were separated with acceptable resolution with the developed chromatofocusing method. The chromatofocusing profile of the studied conjugated antibody demonstrated its charge heterogeneity with pI values ranged from 7.3 to 8.5. The developed chromatofocusing method was applied for monitoring the stability of studied conjugated antibody under stress conditions.